METAPHORICAL EXPRESSION USED IN POETRY IN ENGLISH TEXTBOOK ENTITLED "PATHWAY TO ENGLISH" - Ketaren, Serefina Veronika; Br. Pakpahan, Emma Martina (PROJECT (Professional Journal of English Education), 2021)
The aims of this research are to find out the types and meaning of metaphor in poetry in English textbook entitled “Pathway to English”. The main data of this research are 9 poetry in the English textbook entitled “The Seasons”, “The Little Rose Tree”, “Alpine Glow”, “From Alcuin”, “A Man Young and Old: Human Dignity”, “Love and Friendship”, “Mountain”, “My Star”, and “I Wandered Lonely as a Cloud”. In this research the researcher applied descriptive qualitative method to analyze the data. The researcher used theory of Parera to classify the types of metaphor and also used the metaphor identification procedure proposed by Pragglejaz to identify the metaphors contained in the poetry. The result showed that there are 22 lines that used metaphor, which 16 lines are anthropomorphic metaphor, 3 lines are synesthetic metaphor, 2 lines are metaphor abstract to concrete and 1 line is animal metaphor. The meaning of all these poetry is about life. By using metaphor the poet can also express their feelings to the reader to understand the implicit message contained in the poetry through the depiction or comparison made by the poet.